Exploration of Problems, Prospects and Marketing Potential of Game Poultry Birds in Nepal - Baskota, N; Acharya, M.P.; Upreti, S; Dahal, M; Shrestha, S (Nepalese Veterinary Journal, 2023)
Available within full article